Pengembangan Multimedia Interaktif Dalam Pembelajaran IPS Materi Sumber Daya Alam Kelas IV SD/MI - Handoko Fiadi Prayitno; Riyan Abdul Aziz; Hadis Turmudi (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Early natural resource education can help improve individual attitudes in preserving the environment. The author develops learning media focusing on understanding natural resource material. The goal is to provide students with effective and efficient skills in understanding the types, distribution, and process of natural resource formation through visualization, not just memorizing. The development of this interactive media uses Adobe Animate CC 2023 with the hope of attracting students' interest and supporting teacher teaching. The ADDIE method is used to develop interactive multimedia products. This media consists of learning materials and interactive quizzes, supports the teacher's role and provides students with an understanding of Social Sciences (IPS) lessons about natural resources. Interactive multimedia learning media has a positive impact on social studies natural resources learning. This approach motivates students, provides independence, and introduces alternative methods. Thus, the interactive multimedia approach contributes to the effectiveness and interactivity of learning natural resources.